W poszukiwaniu racjonalnej organizacji społeczeństwa. Tomasz More, Robert Owen a praktyka kibuców - Grudzińska, Agata (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the article is to present and analyze selected organizational solutions based on the same principles thanks to which their creators wanted to create the perfect social order. I will try to demonstrate the rationality of these solutions using the example of the state of T. More, New Harmony of R. Owen and kibbutzes in Israel. Certain regularities can be observed in that the emergence of fundamental assumptions of these communities coincides with the moments of crisis in particular societies, which led to changes in the way people think about the world around them. The object of the research is an understanding of the organization of these communities and the effectiveness of their functioning based on the same rules.
Keywords: Morus Tomasz; Nowa Harmonia; kibuce; racjonalność